GABAergic Control of Nigrostriatal and Mesolimbic Dopamine in the Rat Brain - Nikolaus, Susanne; Wittsack, Hans-Jörg; Beu, Markus; Antke, Christina; De Souza Silva, Maria A.; Wickrath, Frijthof; Müller-Lutz, Anja; Huston, Joseph P.; Antoch, Gerald; Müller, Hans-Wilhelm; Hautzel, Hubertus (Frontiers in Behavioral Neuroscience, 2018)
Purpose: The present study assessed the effects the GABAA receptor (R) agonist muscimol (MUS) and the GABAAR antagonist bicuculline (BIC) on neocortical and subcortical radioligand binding to dopamine D2/3Rs in relation to motor and exploratory behaviors in the rat. Methods: D2/3R binding was measured with small animal SPECT in baseline and after challenge with either 1 mg/kg MUS or 1 mg/kg BIC, using [123I]IBZM as radioligand. Motor/exploratory behaviors were assessed for 30 min in an open field prior to radioligand administration. Anatomical information was gained with a dedicated small animal MRI. Based on the Paxinos rat brain atlas, regions of interest were defined on SPECT-MRI overlays. Estimations of the binding potentials in baseline and after challenges were obtained by computing ratios of the specifically bound compartments to the cerebellar reference region. Results: After MUS, D2/3R binding was significantly reduced in caudateputamen, nucleus accumbens, thalamus, substania nigra/ventral tegmental area and posterior hippocampus relative to baseline (.005 ≤ p ≤ .012). In all these areas except for the thalamus, D2/3R binding was negatively correlated with grooming in the first half and positively correlated with motor/exploratory behaviors in the second half of the testing session. After BIC, D2/3R binding was significantly elevated in caudateputamen (p = .022) and thalamus (p = .047) relative to baseline. D2/3R binding in caudateputamen and thalamus was correlated negatively with sitting duration and sitting frequency and positively with motor/exploratory behaviors in the first half of the testing time. Conclusions: Findings indicate direct GABAergic control over nigrostriatal and mesolimbic dopamine levels in relation to behavioral action. This may be of relevance for neuropsychiatric conditions such as anxiety disorder and schizophrenia, which are characterized by both dopaminergic and GABAergic dysfunction.